Daniel F. Littlefield Jr.’s Seminole Burning and the Historiography of the Lynching of Native Americans - Pfeifer, Michael J. (The journal of the gilded age and progressive era, 2021)
[...]a significant number of lynchings of Native Americans occurred in the middle decades of the nineteenth century, as white settlers moved into areas of the developing Midwest and West and clashed with Native American communities, antedating the late nineteenth- and early twentieth-centuries’ chronological focus of data collected by anti-lynching activists and the scholars who have built their studies upon such data. 5 Native Americans also fell out and still fall out of the picture due to yet other aspects of their liminal status that, ironically, also sometimes made them target of mobs of Indian-hating white settlers: subject to Anglo-American military conquest but separated and ostensibly protected from white settlers, at times not subject to territorial and state laws, wards of the federal government, and members of sovereign Native nations and participants in Native legal cultures. 6 While anti-Indian collective violence often took the form of state-sponsored warfare and massacre by the U.S. army, white settlers’ anti-Indian animus sometimes cascaded into genocidal massacre but sometimes also took the form of lynching, collective murder perpetrated by white settlers targeting individual Natives. 7 In short, while the lynching of Natives often occurred in contexts involving confusion or complexity of legal jurisdiction, the continuing dearth of scholarship on anti-Native mob violence stems from how anti-Indian violence has confused and confounded categories of geography, race, and even the very definitions of particular varieties of collective violence (for instance the difference between a massacre and a lynching) that have long bounded scholarship on American lynching. The extensive documentation of the case flowed from the ultimately successful federal prosecution of a number of the lynchers for crimes they committed in kidnapping the Natives in Indian Territory and removing them to Oklahoma Territory for the mob execution. [...]here the unique legal status of Natives—and the strong political interest in Congress in prosecuting the case in order to smooth the allotment of tribal lands and the absorption of the Indian Territory into Oklahoma Territory—created a federal interest in a lynching case that was almost unheard of in contemporaneous lynchings of African Americans. 10 Yet the lynchers at Maud sought vindication and white communal support in Oklahoma Territory by instead seeking to represent their actions as those of a mass mob, most significantly by inventing an allegation that Mary Leard had been raped by her Native assailant(s) before she was murdered and also by circulating news for days of an impending burning of Natives to attract white participants from the surrounding region to the lynching. [...]the Oklahoma Territory lynchers of Natives consciously imitated Southern lynchers of African Americans and sought to deploy arguments white Southerners often used to defend the actions of mass mobs; indeed one of the ringleaders in the lynching, Samuel V. Pryor, an extended kinsman of the murdered woman, argued that he had expertise in lynching African Americans, as he had supposedly participated in the lynching by immolation of an African American in Texas. 11 Assessing the field of lynching studies some twenty-five years after Brundage’s Lynching in the New South and twenty-two years after the publication of Seminole Burning, Littlefield’s book remains the most significant monograph on the lynching of Native Americans. Beyond his deeply etched reconstruction of the racially motivated mob murders of the young Seminole men, Littlefield’s strong familiarity with both Native and American legal cultures and sources enabled him to deftly interpret the legal ambiguities and the complex texture of Native-white relations on the periphery of Indian Territory that informed the mob murders of McGeisey and Sampson.